Um estudo sobre a história da histeria e das histéricas - Pereira, Erica do Nascimento Hora (2022)
The present research proposes to study the history of hysteria, of the doctors who treated and studied it, and of some hysterical women. Thus, we take as a starting point the study of Mesmer and his magnetic treatments in the 18th century, passing through the clash between the schools of Salpêtrière and Nancy at the end of the 19th century, reaching the conceptions of Freud's psychoanalysis in the 20th century, describing the entire treatment of hypnosis in which the doctor exercised authority in relation to patients and later when women put themselves as the conductor of their own stories. We are also interested in the impact that hysteria has on culture, with its inscriptions in the field of politics, in which hysterics are considered militants of anti-psychiatry, because they question the role of the doctor in charge, until then, of attesting to the truth of the disease in the hospital space. . It is a bibliographical research, of a historical nature, that wants to recognize the life and voice of hysterical women, so often denied by their doctors.